Scandology 3 scandals in new media - Haller, André 1984-; Michael, Hendrik; Seeber, Lucas (Springer, 2021)
Introduction -- Part 1 - Scandals and Digital Publics: Transformations of Power and Visibility -- Social Amplification of Scandals: One Social Media Effect -- Scandalous Criticism in the Speakers’ Corner: Online and Offline Reactions to Rezo’s The Destruction of the CDU and Jan Böhmermann’s #neustart19 -- Are we living in a post scandal era? High-choice media environments, political polarization and their consequences for political scandals -- Part 2 - Forms, Functions, and Practices of Scandal Reporting in changing Media Environments -- Gossip as journalism and journalism as gossip: A cultural history investigation of two royal sex scandals in Sweden 1890 and 2010 -- Italian newspapers and corruption scandals coverage: the construction of the "parallel trial" -- Part 3 - Scandals, New Media and the Historical Perspective -- Early Modern Sermon and Scandalization? The Sermons of the Jesuit Georg Scherer (1540-1605) -- Revenge for Caligula!" Ludwig Quidde, Wilhelm II and the scandal of 1894 -- Having the Last Laugh: Scandalous Character Assassination in Comedy in Classical Athens and the Current-Day United States -- Part 4 - New Media, Scandals in Culture, and Public Protest -- Hips don’t lie: Visual resistance to discoursal normalization of sexual violence in the Israeli SlutWalk movement -- Scandalogy Meets Field Theory. Utilizing Scandal Theory for the Analysis of Journalistic Practices Over Time -- "The Voice Kids" Scandal in Russia: How the Voiceless Found Their Voice
Keywords: Neue Medien; Skandal -- Motiv; Political communication; Digital media; Political science; Journalism; Social media; Konferenzschrift -- 2021; Aufsatzsammlung